Faecal microbiota transplantation protects against radiation‐induced toxicity - Ming Cui; Huiwen Xiao; Yuan Li; Lixin Zhou; Shuyi Zhao; Dan Luo; Qisheng Zheng; Jiali Dong; Yu Zhao; Xin Zhang; Junling Zhang; Lu Lu; et al. (EMBO Molecular Medicine, 2017)
Abstract Severe radiation exposure may cause acute radiation syndrome, a possibly fatal condition requiring effective therapy. Gut microbiota can be manipulated to fight against many diseases. We explored whether intestinal microbe transplantation could alleviate radiation‐induced toxicity. High‐throughput sequencing showed that gastrointestinal bacterial community composition differed between male and female mice and was associated with susceptibility to radiation toxicity. Faecal microbiota transplantation (FMT) increased the survival rate of irradiated animals, elevated peripheral white blood cell counts and improved gastrointestinal tract function and intestinal epithelial integrity in irradiated male and female mice. FMT preserved the intestinal bacterial composition and retained mRNA and long non‐coding RNA expression profiles of host small intestines in a sex‐specific fashion. Despite promoting angiogenesis, sex‐matched FMT did not accelerate the proliferation of cancer cells in vivo. FMT might serve as a therapeutic to mitigate radiation‐induced toxicity and improve the prognosis of tumour patients after radiotherapy.